The Correlation between Self-Talk and Speaking Ability - Muhammad Syahruramadana Syukur; Hastini Hastini; Maf'ulah Maf'ulah (Hasanuddin University, 2025)
This research used correlational quantitative research design. This research aims to find out whether there is a positive correlation between students' self-talk and their speaking’s ability. The sample of this research consists of 30 students from the academic year 2021/2022 of English Education Study Program at Tadulako University. The sampling technique used in this study is simple random sampling. The instruments used to collect data were a speaking test and a questionnaire. The method used to analyze the correlation between students' self-talk and students' speaking ability is the Pearson product-moment correlation and simple linear regression test. The result of this research showed that there is a significant correlation between self-talk and students’ speaking ability. This correlation is indicated by a Pearson correlation value of 0.883, which means there is a very strong correlation between the two variables. The value of t-count is 9.975, higher than the t-table 2.048. This implies that students’ self-talk can influence the development of speaking ability. The higher the positive self-talk that students have, the better their speaking ability will be. Conversely, the higher the negative self-talk that students have, the lower their speaking ability will be.